Clinical and radiographic assessment of the association between orthodontic mini-screws and periodontal health - Mehmet Selim Yildiz; Pelin Acar Ulutas; Ilknur Ozenci; Aliye Akcalı (BMC, 2024)
Abstract Objectives Proper anchorage control is crucial for predictable tooth movement and preventing inadequate torque during orthodontic treatment. Through clinical and radiographic parameters; this study assesses the association between mini-screws and periodontal health. Materials and methods A prospective observational study included 16 systemically healthy non-smoking individuals requiring mini-screws. Mini-screws with a rough, titanium oxide-coated surface were placed. Periodontal assessments (Plaque index, gingival index, probing pocket depth, gingival recession, bleeding on probing, mucosal discomfort, mucosal redness, keratinized tissue width, supracrestal tissue height, and transmucosal soft tissue thickness) were performed at 2nd week and 3 months post-placement. Radiographic evaluations measured distances between mini-screws and adjacent teeth using Image J software. Results The study included 13 females and 3 males (mean age 21.9 ± 1.8 years) with 24 mini-screws. Early mini-screw loss was not observed. Significant reductions in site-level Gingival Index and bleeding on probing (p < 0.05) and full-mouth bleeding on probing (p < 0.05) were noted over time. Absence of significant differences was found in mucosal discomfort and redness, keratinized tissue width, or transmucosal soft tissue thickness, but supracrestal tissue height decreased significantly (p < 0.05). Radiographically, significant bone reduction around mini-screws was observed at 3 months, with torque gauge values significantly decreased as well (p < 0.05). Conclusions Orthodontic mini-screws can be effectively utilized in orthodontic treatment with proper planning and monitoring. While improvements in gingival health were observed with targeted oral care, the study underscores the need for careful consideration of potential risks to periodontal tissues, such as reductions in supracrestal tissue height and bone levels. A balanced approach that integrates preventive strategies with precise screw placement is essential to maximize the benefits of mini-screws while minimizing potential periodontal complications. Clinical relevance While proper oral hygiene can help control inflammation around mini-screw sites, clinicians must also be mindful of potential risks, such as reductions in bone levels and tissue height. Careful patient selection, precise placement, and regular follow-up are crucial to ensure the stability of mini-screws' stability and to prevent complications, ultimately contributing to better treatment outcomes in orthodontic care. Trial registration This study was registered on ClinicalTrials.gov with the registration number NCT06491849 on June 28, 2024.